TEACHING MATHEMATICS WITH THE USE OF DIGITAL LEARNING PLATFORMS: ANALYSIS OF FOREIGN EXPERIENCE - Matiash, Olha; Ryndiuk, Valentyn (Physical and Mathematical Education, 2023)
Formulation of the problem. The Ukrainian methodological science is faced with the task of studying and analyzing the domestic and foreign experience of using digital educational platforms within the school’s mathematical education to clarify scientifically grounded recommendations for mathematics teachers on effective interaction with the modern digital environment to overcome current challenges. This article reviews foreign experiences of using educational platforms during the teaching process and analyzes the results of research on the impact of using digital learning platforms on the organization and quality of teaching mathematics in different countries. Materials and methods. Articles created by researchers from Latvia, Spain, Turkey, Mexico, Denmark, USA. Analysis, systematization, and generalization of the results of the research which are reflected in the publications of foreign authors. Results. The analysis of publications made it possible to find out: the content of the concept of "educational platforms"; the prevalence of using educational platforms in a particular country; the results of the research on the effectiveness of using educational platforms. Designing and further development of cloud-oriented learning environment is one of the key directions of education development in Latvia, Spain, Turkey, Mexico, Denmark, USA. The authors of the publications investigate the impact of e-learning and indicate the relevance and insufficiency of such studies. Main results: educational platform is a tool in the hands of the teacher who can make this tool effective; educational platforms open a wide range of opportunities for teachers of mathematics to improve their students` learning efficiency; even the existence of educational platforms with the highest quality does not exempt teachers from painstaking methodological work. Conclusions. The combination of foreign experience in using digital educational platforms with the potential of Ukrainian scientists’ research is one of the directions for further implementation of innovative technologies into the Ukrainian education system. The purpose of our subsequent research is to continue the analysis of the foreign experience in using digital educational platforms within school education and the in-depth study and analysis of the educational value and pedagogical potential of educational platforms that are used in Ukraine within the process of teaching mathematics to the pupils of the high school.